An assessment of climate change effects on atmospheric corrosion rates of steel structures. (August 2013) - Nguyen, M N; Wang, X; Leicester, R H
Abstract : This paper presents a discussion on assessing the potential impacts of climate change on the atmospheric corrosion rates of exposed steel structures. The effects on atmospheric corrosion due to changes in the environmental temperature, carbon dioxide, relative humidity, wind, rainfall and pollution are considered. The limitations and complexities of these assessments are discussed. To demonstrate the use and limitations of this science to evaluate effects related to climate change, a model developed in Australia to predict corrosion is combined with climate change models to project the change in the corrosion rates of steel components and protective zinc coatings in constructions. The method is applied to constructions located along the coastal areas of two Australian cities: Melbourne and Brisbane. These assessments are made using the A1FI scenario, the highest emission scenario defined by the Intergovernmental Panel on Climate Change, applied to nine general circulation models. The projected changes in corrosion rates were found to be an increase of ∼14% for both zinc and steel in Brisbane and a decrease of ∼14% for steel and 9% for zinc in Melbourne. It was also found that the uncertainties associated with the climate change models were small compared to those involved in modelling corrosion for engineering purposes.